2019
DOI: 10.1111/sdi.12841
|View full text |Cite
|
Sign up to set email alerts
|

Anemia management in cancer patients with chronic kidney disease

Abstract: Cancer and kidney disease are linked by causality and comorbidities. Observational data show an increased risk of malignancy as renal function declines. Erythropoietin stimulating agents (ESAs), which are the cornerstone therapy for anemia patients with chronic kidney disease and cancer, are associated with increased risks for cancer, cancer‐related mortality, progression of disease, and thromboembolic events. This article examines the recently published guidelines for ESA use in cancer patients from the Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…[43][44][45][46] In addition, in vitro and in vivo studies have indicated that ESAs may be involved in promoting tumor progression. [47][48][49][50][51] ESAs bind to and activate erythropoietin receptors, thereby stimulating pathways involved in cellular differentiation, proliferation, and prevention of apoptosis, including the Janus-activated 2/signal transducer and activator of transcription 5, phosphoinositide 3-kinase/protein kinase B, and Ras/extracellular signal-regulated kinase pathways. [47][48][49][50][51] Furthermore, no guidelines exist for nephrologists regarding the use of ESA therapy in anemic CKD patients with cancer.…”
Section: Management Of Anemia Of Ckd In Patients With Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45][46] In addition, in vitro and in vivo studies have indicated that ESAs may be involved in promoting tumor progression. [47][48][49][50][51] ESAs bind to and activate erythropoietin receptors, thereby stimulating pathways involved in cellular differentiation, proliferation, and prevention of apoptosis, including the Janus-activated 2/signal transducer and activator of transcription 5, phosphoinositide 3-kinase/protein kinase B, and Ras/extracellular signal-regulated kinase pathways. [47][48][49][50][51] Furthermore, no guidelines exist for nephrologists regarding the use of ESA therapy in anemic CKD patients with cancer.…”
Section: Management Of Anemia Of Ckd In Patients With Cancermentioning
confidence: 99%
“…[47][48][49][50][51] ESAs bind to and activate erythropoietin receptors, thereby stimulating pathways involved in cellular differentiation, proliferation, and prevention of apoptosis, including the Janus-activated 2/signal transducer and activator of transcription 5, phosphoinositide 3-kinase/protein kinase B, and Ras/extracellular signal-regulated kinase pathways. [47][48][49][50][51] Furthermore, no guidelines exist for nephrologists regarding the use of ESA therapy in anemic CKD patients with cancer. 52 The long-term effects of iron supplementation on clinical outcomes, including cardiovascular events, hospitalization, and mortality, as well as the safety of iron therapy in patients with cancer and CKD, are unknown.…”
Section: Management Of Anemia Of Ckd In Patients With Cancermentioning
confidence: 99%
“…Anemia is a common consequence of CKD, especially in advanced stages; more than 50% of ESRD patients have anemia [30]. A decline of erythropoietin (EPO) production is commonly experienced [31] due to a reduction in renal function [32].…”
Section: Anemiamentioning
confidence: 99%
“…Erythropoiesis-stimulating agents (EAS) have been considered the best treatment for managing anemia in CKD patients since they became available in 1989 [30]. Although the use of ESAs has improved conditions in CKD, RCTs have questioned the safety of the duration in treatment and the use of high dose ESAs to normalize hemoglobin (Hb) levels [38].…”
Section: Anemiamentioning
confidence: 99%
See 1 more Smart Citation